Biodegradable resistive switching memory based on magnesium difluoride. Issue 32 (1st August 2016) - Zhang, Zhiping; Tsang, Melissa; Chen, I-Wei
Abstract : This study presents a new type of resistive switching memory device that can be used in biodegradable electronic applications. Abstract : This study presents a new type of resistive switching memory device that can be used in biodegradable electronic applications. The biodegradable device features magnesium difluoride as the active layer and iron and magnesium as the corresponding electrodes. This is the first report on magnesium difluoride as a resistive switching layer. With on–off ratios larger than one hundred, the device on silicon switches at voltages less than one volt and requires only sub-mA programming current. AC endurance of 10 3 cycles is demonstrated with ±1 V voltage pulses. The switching mechanism is attributed to the formation and rupture of conductive filaments comprising fluoride vacancies in magnesium difluoride. Devices fabricated on a flexible polyethylene terephthalate substrate are tested for functionality, and degradation is subsequently demonstrated in de-ionized water. An additional layer of magnesium difluoride is used to hinder the degradation and extend the lifetime of the device.